Sexual assault in the U.S. military: the battle within America's armed forces - Skaine, Rosemarie (Praeger security international, 2016)
Sexual assault in the military and society -- Sexual assault scandals in the military -- Policies and laws -- Jurisdiction and courts -- Women -- Men -- Sexual assaults on gay, lesbian, bisexual and transgendered service member -- The impact of sexual assault on the military -- Approaches to reduce or eliminate sexual assault in the military -- Appendices -- A. 2014 National Defense Authorization Act: selected sections on sexual assault -- B. Repeal of "Don't Ask, Don't Tell" -- C. President Obama's charge to the military on sexual assault --D. President Obama proclaims June 2015 as LGBT month -- E. President Obama initiates the "It's on Us" campaign -- F. Selected sections of the Uniform Code of Military Justice Law, 1949 -- G. Department of Defense Directive, Number 1304.26, December 21, 1993